Master or apprentice: rethinking entry points and training in Public Health. (19th July 2017) - Shickle, Darren; Stroud, Laura; Day, Matthew; Smith, Kevin
Abstract: Background: The Public Health workforce needs to adapt to a policy environment in which the need to improve public health is not only a key challenge but also has to be delivered within financial constraints. Methods: A total of 14 qualitative individual interviews or focus groups (of up to 10 people), were conducted with senior Public Health staff in 12 local authorities and in Public Health England in the Yorkshire and the Humber region of England. Thematic analysis was applied to the transcribed interviews. Results: Despite cuts in training budgets, junior staff were increasingly expected to deliver Public Health functions. There is also an absence of a career ladder for this core Public Health workforce. There were concerns that financial constraints would lead to reductions in Public Health skills with fewer staff to provide critical analysis. Formal qualifications were increasingly less valued. Instead staff were expected to have a broader skill set with an emphasis on experience. Entry points into Public Health careers need rethinking. There was an expectation that Public Health departments would 'grow their own'. Conclusions: Apprenticeship schemes could help maintain or enhance the professional status of Public Health and provide a training route for Public Health practitioners.